2017
DOI: 10.1097/hco.0000000000000413
|View full text |Cite
|
Sign up to set email alerts
|

Imaging pathobiology of carotid atherosclerosis with ultrasmall superparamagnetic particles of iron oxide

Abstract: Purpose of reviewTo provide brief overview of the developments regarding use of ultrasmall superparamagnetic particles of iron oxide in imaging pathobiology of carotid atherosclerosis.Recent findingsMRI is a promising technique capable of providing morphological and functional information about atheromatous plaques. MRI using iron oxide particles, called ultrasmall superparamagnetic iron oxide (USPIO) particles, allows detection of macrophages in atherosclerotic tissue. Ferumoxytol has emerged as a new USPIO a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 31 publications
2
11
0
Order By: Relevance
“…Preclinical studies showed that it induces larger signal changes in the plaque than Sinerem [ 39 , 40 ]. Ferumoxytol has been used to image myocardial inflammation [ 41 , 42 ], and is being evaluated for monitoring inflammation in carotid atherosclerosis [ 20 , 22 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Preclinical studies showed that it induces larger signal changes in the plaque than Sinerem [ 39 , 40 ]. Ferumoxytol has been used to image myocardial inflammation [ 41 , 42 ], and is being evaluated for monitoring inflammation in carotid atherosclerosis [ 20 , 22 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Quantitative imaging, in principle, allows for quantification of iron concentration. Quantitative imaging of USPIO in atherosclerosis mostly focused on techniques such as T 2 * mapping [ 13 , 14 , 17 , 20 , 21 , 22 ] and susceptibility gradient mapping [ 15 , 23 ]. However, in vasculature that is heavily affected by cardiac and respiratory motion, such as the arteries near the heart, the latter techniques are prone to movement artifacts, which negatively affects their quantitative power.…”
Section: Introductionmentioning
confidence: 99%
“…The potential of this imaging technique as a diagnostic tool to visualize macrophage-mediated inflammatory responses in situ has already been indicated in several diseases like atherosclerosis, cancers, and inflammation in the central nervous system. 18,[20][21][22][23][24] In this section, we have summarized the previous experimental findings and a rationale to use the presence of macrophages as a surrogate marker to predict the progression or rupture of IAs.…”
Section: Macrophage Infiltration As a Surrogate Marker To Predict Thementioning
confidence: 99%
“…Indeed, macrophage imaging using USPIO has been demonstrated in oncology and inflammation in the central nervous system. 18,[20][21][22][23][24] Ferumoxytol has 30 nm in the hydrodynamic diameter and its circulating half-life is about 14 h in human. Because the diameter of ferumoxytol is remarkably smaller than well-used gadolinium-containing contrast agent with the diameter 1 nm and is thus retained much longer in the blood, ferumoxytol disappears much more slowly from blood stream but may cross the impaired blood-brain barrier more specifically Figs.…”
Section: Macrophage Imagingmentioning
confidence: 99%
“…The size of these MNPs is 50 nm which have been coated with polystyrene to obtain 3.5μm particles. 102 These MNPs are mainly used to take pictures from liver / spleen / lymph nodes in patients with pelvic, prostate, bladder, or breast cancer, and this process is briefly elaborated here. Relatively, iron oxide MNPs of large size are used for liver / spleen imaging such as AMI-25 (Feridex ® / Endorem TM , DH = 80–200 nm) and SHU 555A (i.e., Resovist ® / Cliavist TM , DH = 60 nm).…”
Section: Function and Application Of Mnpsmentioning
confidence: 99%